Proceedings of the Asia Pacific Business and Economics Conference (APBEC 2018) 2019
DOI: 10.2991/apbec-18.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Islamic Social Reporting in Indonesia and Malaysia

Abstract: This paper aims to examine the determinants of Islamic Social Reporting (ISR) disclosure levels and examine whether legal origins affect ISR disclosure levels. This study examined samples from Islamic banks in Indonesia and Malaysia between 2013 and 2015 using regression analysis. The result shows that a bank's size and age positively affect ISR disclosure level. Profitability negatively affects ISR disclosure level, and the number of Sharia Supervisory Boards did not affect ISR disclosure level. Legal origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 19 publications
1
13
1
1
Order By: Relevance
“…However, other studies have come out strongly stating that a higher profitability level does not guarantee an increased level of ISR disclosure of Islamic banks (Anggraini & Wulan, 2017). Other studies, such as by Hajawiyah et al (2019), found that an increased level of profitability will often decrease a firm's level of ISR disclosure.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, other studies have come out strongly stating that a higher profitability level does not guarantee an increased level of ISR disclosure of Islamic banks (Anggraini & Wulan, 2017). Other studies, such as by Hajawiyah et al (2019), found that an increased level of profitability will often decrease a firm's level of ISR disclosure.…”
Section: Resultsmentioning
confidence: 97%
“…This is done for them to strengthen their position and gain legitimacy among its stakeholders. Most studies in this area show that firm size has a positive influence on the ISR disclosure of a bank (Hajawiyah et al, 2019;Mukhibad, 2018 cited above, several studies fail to show a relationship between firm size and their level of ISR disclosure (Kasih & Rini, 2018;Prasetyoningrum, 2018;Widayuni & Harto, 2014).…”
Section: The Effect Of Firm Size On Isr Disclosurementioning
confidence: 99%
“…As of January 2012, Malaysian accounting standards were in congruence with the International Financial Reporting Standards (IFRS). In support of this, Hajawiyah et al (2019) also argued that legal has significant implications on the level of ISR disclosure in Malaysia and Indonesia.…”
Section: Jfrc 294mentioning
confidence: 95%
“…Similarly, ST argues that corporation would be willing to disclose more to get public attention because the benefit of the ISR disclosure outweighs the cost. ST further argues that business decision should consider the interest of all concern parties (Hajawiyah et al, 2019). As a result, different studies investigate relationship between ISR and corporate performance while focusing on ST (Oyewumi et al, 2018;Hajawiyah et al, 2019;Indayani et al, 2019;Sofian and Muhamad, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation